2005
DOI: 10.1042/bj20050404
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional differences in isoforms of mouse major urinary proteins: a male-specific protein that preferentially binds a male pheromone

Abstract: The MUPs (major urinary proteins) of the house mouse, Mus domesticus, are lipocalins that bind and slowly release male-specific pheromones in deposited scent marks. However, females also express these proteins, consistent with a second role in encoding individual signatures in scent marks. We have purified and characterized an atypical MUP from the urine of male C57BL/6J inbred mice, which is responsible for the binding of most of the male pheromone, 2-sec-butyl-4,5-dihydrothiazole, and which is also responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(122 citation statements)
references
References 32 publications
6
114
0
1
Order By: Relevance
“…It is a member of the major urinary protein family, MUP20 (MGI:3651981), which shows a strongly malebiased expression and a molecular weight of 18893Da. Being a lipocalin, darcin binds small lipophilic molecules, with high affinity for thiazoline (Armstrong et al, 2005) which, as discussed above, is a volatile compound also present in male (but not female) urine. Although some pheromonal activities have been proposed for thiazoline, including attraction (together with brevicomin, but not alone), oestrous synchronisation and puberty acceleration 1989;Novotny et al, 1999), its role in intersexual attraction must be negligible since recombinant darcin obtained in E. coli, free of ligands, is attractive when compared to buffer or to full female urine.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…It is a member of the major urinary protein family, MUP20 (MGI:3651981), which shows a strongly malebiased expression and a molecular weight of 18893Da. Being a lipocalin, darcin binds small lipophilic molecules, with high affinity for thiazoline (Armstrong et al, 2005) which, as discussed above, is a volatile compound also present in male (but not female) urine. Although some pheromonal activities have been proposed for thiazoline, including attraction (together with brevicomin, but not alone), oestrous synchronisation and puberty acceleration 1989;Novotny et al, 1999), its role in intersexual attraction must be negligible since recombinant darcin obtained in E. coli, free of ligands, is attractive when compared to buffer or to full female urine.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…In one prominent example, distinctive profiles of MUPs are expressed in different strains, as well as in different subspecies, of mice (Robertson et al 1996;Stopková et al 2007). An atypical MUP that preferentially binds to 2-sec-butyl-4,5-dihydrothiazole is male-specific (Armstrong et al 2005). Variation in MUPs is extensive in wild populations, where they are involved in individual recognition (Hurst et al 2001;Cheetham et al 2007), inbreeding avoidance (Sherborne et al 2007) and evaluation of genetic heterozygosity of potential mates (Thom et al 2008).…”
Section: Mhc Odourtypes and Complexity Of Individual Odour Signaturesmentioning
confidence: 99%
“…Methylation analysis revealed that the Major Urinary Protein 4 (MUP4) is one of the candidate imprinted-like genes induced in the vinclozolin generation males [17]. This MUP group of gene products binds and releases male-specific pheromones in rodents [5,19]. Finally, to rule out odor discrimination capacity as a potential explanation for their failure to show a preference in the mate preference test, we established that both males and females explored odors of the opposite sex much more than familiar (self) odors or novel odors of the same sex, and all animals explored novel odors of the same sex more than self odors.…”
Section: Transgenerational Epigenetic Imprint On the Nuclear Genome Amentioning
confidence: 99%